European payment order - collection of overdue receivables from foreign legal and natural persons - Nižić-Peroš, Jadranka (Oeconomica Jadertina, 2022)
The subject of this paper is an analysis of legislation and case law related to the issuance of a European payment order and the purpose of this paper is to provide incentives to legal and natural persons for future use of this instrument applied in the Republic of Croatia since July 2013, which is used in an extremely small number of cases. The courts are competent for issuing a European payment order in the Republic of Croatia and it is an instrument that collects claims from foreign legal and natural persons, debtors, without the need to know the languages of the European Union. Therefore, the application of the payment order procedure enables simple, fast and cheap court collection of the claim from the debtor, assuming that the claim will not be disputed by the debtor. The European payment order is an alternative procedure compared to the procedure carried out at national level, and the greatest advantage of this procedure is its practicality as it is necessary to submit only one request on the prescribed form available in the languages of all EU countries, available to everyone at the Internet portal e-pravosudje. The paper analyses the issuance of a payment order by EU member states, except Denmark, since creditors from the Republic of Croatia can request the issuance of a European payment order against their debtors directly in all other EU member states. We start from the point of view that in the business world uncollected overdue receivables from foreign legal and natural persons are a big problem, and that by joining the European Union, creditors are enabled to collect their receivables from debtors living in one of the EU countries in a quick and easy way, about which according to the author, creditors do not have sufficient knowledge. Application of Regulation (EC) no. 1896/2006, which regulates the procedure for issuing a European payment order, is extremely important precisely because its application ensures equal conditions for the collection of undisputed (uncontested) civil and commercial claims throughout the European Union except Denmark.
Keywords: European payment order; overdue receivables; cross - border cases; collection of debt